The Impact of a Merger on Changes in Organizational Culture: A Systematic Literature Review - Foelyati, Rika; Dudija, Nidya (International Journal of Science, Technology & Management, 2024)
This systematic literature review aims to assess the impact of changes in organizational culture within companies undergoing mergers. The methodology involved an extensive search and selection of peer-reviewed articles published between 2017 and 2023. The research process included gathering information through detailed interviews with employees directly involved in the merger process and analyzing company documents. The study identifies several effects of changes in organizational culture during mergers, such as feelings of uncertainty, concerns about losing corporate identity, and challenges in integrating different cultures. However, it also indicates that mergers can create synergy and long-term benefits if the new organizational culture is successfully integrated. Through empirical analysis, this research uncovers the characteristics, values, and norms that define post-merger organizational culture. It contributes not only to the academic understanding of organizational behavior and change but also offers valuable insights for practitioners in the telecommunications industry who face the complexities of post-merger integration.